Edukasi Kesehatan Mental untuk Pencegahan Gangguan Psikologis pada Remaja di SMK Kesehatan Pro-Skill Indonesia, Pekanbaru - Ikhsan Nursyafik; Nichita Khairun Nisya; Chica Zahwa Naira Melani Ginting; Nesaliya Azhari; Rusda Aulia; Kiki Zein Yulivia; Syahwa Elmina Safitri; Yogi Candra; Rafinda Rafinda; M. Rusydy (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2026)
Mental health education was conducted at SMK Kesehatan Pro‑Skill Indonesia, Pekanbaru, with the aim of increasing knowledge, awareness, and coping skills among adolescents as an effort to prevent psychological disorders. As many as 150 tenth-grade students participated in the activity on May 08, 2026. The intervention took the form of a counseling session titled "Teenagers and Mental Status: Are You Ready to Face Pressure," featuring audiovisual media, interactive lectures, group discussions, and Q&A sessions. The evaluation was conducted in one day, with a pre-test before the presentation of the material and a post-test immediately after the material was completed. The results showed an increase in average knowledge from 45.2% (SD = 12.3) to 78.6% (SD = 10.1) (mean diff = 33.4, paired t = 35.6, p < 0.001). This intervention has proven effective at instantly increasing mental health literacy, though the sustainability of its effects remains to be evaluated.